2021
DOI: 10.1111/cmi.13385
|View full text |Cite
|
Sign up to set email alerts
|

Host cell membrane microdomains and fungal infection

Abstract: Lipid microdomains or lipid rafts are dynamic and tightly ordered regions of the plasma membrane. In mammalian cells, they are enriched in cholesterol, glycosphingolipids, Glycosylphosphatidylinositol-anchored and signalling-related proteins. Several studies have suggested that mammalian pattern recognition receptors are concentrated or recruited to lipid domains during host-pathogen association to enhance the effectiveness of host effector processes. However, pathogens have also evolved strategies to exploit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 99 publications
(134 reference statements)
1
4
0
Order By: Relevance
“…Hahn et al (2003) found that blocking LacCer using a specific anti-LacCer antibody markedly decreased the release of macrophage inflammatory protein (MIP-2). Similar results were obtained using GSLs inhibitors (N-butyldeoxyno jirimycin and d-threo-1-phenyl-2-decanoylamino-3-morpholino-1propanol-HCl), suggesting that LacCer may also play a significant role in inducing β-glucan-induced inflammatory signaling of P. jirovecii pathogenesis (Hahn et al, 2003;Souza et al, 2021).…”
Section: Pneumocystis Jiroveciisupporting
confidence: 74%
See 2 more Smart Citations
“…Hahn et al (2003) found that blocking LacCer using a specific anti-LacCer antibody markedly decreased the release of macrophage inflammatory protein (MIP-2). Similar results were obtained using GSLs inhibitors (N-butyldeoxyno jirimycin and d-threo-1-phenyl-2-decanoylamino-3-morpholino-1propanol-HCl), suggesting that LacCer may also play a significant role in inducing β-glucan-induced inflammatory signaling of P. jirovecii pathogenesis (Hahn et al, 2003;Souza et al, 2021).…”
Section: Pneumocystis Jiroveciisupporting
confidence: 74%
“…Histoplasma capsulatum is a dimorphic fungus responsible for histoplasmosis, one of the most frequently occurring invasive fungal pulmonary infections (Gnat et al, 2021;Souza et al, 2021). This pathogen produces a cell surface 60 kDa heat shock protein (HSP60) which recognizes complement receptor 3 (CR3) on macrophages, leading to H. capsulatum HSP60 internalization.…”
Section: Histoplasma Capsulatummentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, our group demonstrated the relationship between the organization of lipid microdomains (LD) and the process of H. capsulatum yeast internalization by macrophages [ 102 ]. LDs are dynamic and highly organized regions of the plasma membrane that contain or recruit pattern recognition receptors during pathogen–host interaction [ 103 ]. LD favor recruitment and clustering of receptors and co-receptors impacting ligand recognition and signaling transmission between pathogens and host cells [ 104 ].…”
Section: Pathogenesismentioning
confidence: 99%
“…Finally, CD18 mobilization to lipid microdomains was reduced in macrophages from B4galnt1 −/− . It appears that LD assembly is relevant for a correct and stable recognition of H. capsulatum by macrophages [ 102 , 103 ]. The absence of LD components apparently delays the integrin mobility, modifying the adhesion kinetic and consequently, the dynamic of fungal internalization, a process in which, the involvement of lipid rafts and associated protein-lipid diffusion has been implied [ 105 ].…”
Section: Pathogenesismentioning
confidence: 99%